Complexity of diagnosis and management of a giant thyroid nodule: A case report and a concise literature - Firdausa, Sarah; Zufry, Hendra; Ekadamayanti, Agustia S.; Sucipto, Krishna W.; Burhan, Henry W.; Pratama, Sergio; Benalcazar, Andrés MMB. (Narra Sains Indonesia, 2023)
It is crucial for doctors to decide whether a thyroid nodule is benign or malignant when a patient presents with one, as it will significantly impact how the patient is managed in the future. However, it is not as straightforward to determine between the two; even a physical examination, thyroid function test, ultrasonography, and biopsy have been well performed. It can be more stressful if a patient has an increased risk of malignancy, such as age (below 20- and above 60-year-old), solid nodule, rapid growth, hoarseness, lymphadenopathy, and microcalcifications on the ultrasonography. The aim of this case was to present the management of a giant thyroid nodule with malignancy presentation and a benign biopsy finding. A 41-year-old male complained of a palpable neck mass, hoarseness, and dysphagia. The thyroid function test was normal. Ultrasonography revealed suspicion of malignancy with category 4 of American College of Radiology-Thyroid Imaging Reporting and Data System (ACR-TIRADS). The biopsy revealed follicular neoplasm, and was classified as Bethesda IV. The patient underwent a total thyroidectomy due to the large tumor size and symptoms. Histopathological findings post-surgery revealed a follicular thyroid adenoma. This case highlights a complex diagnosis and management of follicular thyroid neoplasm due to their potential for both benign and malignant. Comprehensive pre- and post-operative care is essential to determine the nature of nodules. Post-operative follow-up care might improve the patient’s outcome and prevent complications.